Improving reading comprehension skills through Know-Want-Learn (KWL) strategy among superior basic education students at a public institution in Loja city, school year 2023-2024 - Gaona Castillo, Sheyli Fernanda (2024)
Reading comprehension is essential to acquire complete mastery of the English language. Therefore, it is vital to develop reading comprehension skills that allow you to understand and analyze texts in various contexts. In this way, the main objective of this research was to demonstrate how the use of the Know-Want-Learn (KWL) strategy improves reading comprehension skills among superior basic education students at a public institution in Loja city, school year 2023-2024. In accordance with this objective, two specific objectives are established: to determine the effectiveness of the Know-Want-Learn (KWL) strategy, and to identify the students’ perceptions about the application of the Know-Want-Learn (KWL) strategy. In this study 24 tenth grade students participated. Furthermore, the research approach used was the mixed method based on action research, since quantitative and qualitative data were integrated. To this end, a pretest and a posttest were applied as quantitative instruments to measure students' knowledge of reading comprehension skills. On the other hand, the questionnaire and field notes served to collect qualitative data on the student's perceptions of the strategy used. The collected data were interpreted using descriptive statistics and analyzed through thematic analysis. Based on this, the results obtained demonstrated that students improved their reading comprehension skills in the aspects: predicting, inferring, summarizing and vocabulary. In addition to this, the results showed a positive impact of the KWL strategy on the students, since they demonstrated greater motivation when carrying out the activities and more interest in the learning process. Consequently, the researcher concluded that the KWL strategy had a positive effect on improving the students' reading comprehension skills, because it encouraged interactive participation and influenced their academic development. Key words: improvement; KWL strategy; reading comprehension skills.